2019
DOI: 10.1051/0004-6361/201935726
|View full text |Cite
|
Sign up to set email alerts
|

Another relic bulge globular cluster: ESO 456-SC38 (Djorgovski 2)

Abstract: Context. The object ESO456-SC38 (Djorgovski 2) is one of the globular clusters that is closest to the Galactic center. It is on the blue horizontal branch and has a moderate metallicity of [Fe/H]∼-1.0. It is thus similar to the very old inner bulge globular clusters NGC 6522, NGC 6558, and HP 1, and therefore appears to be part of the primeval formation stages of the Milky Way. Aims. The aim of this work is to determine an accurate distance and metallicity for ESO456-SC38, as well as orbital parameters, in ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…It may belong to this cluster. Assuming the distance to Djorg 2 is 8.75 kpc (Ortolani et al 2019) and approximate extinction in this direction A V ≈ 2.4 mag (based on the interstellar calculator pro-vided in Nataf et al 2013), we find that the star with the observed brightness F606W ≈ 21.2 mag (broad V band) would have an absolute brightness M V ≈ +4.1 mag, which is a typical value for UCXBs (Nelemans et al 2010).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It may belong to this cluster. Assuming the distance to Djorg 2 is 8.75 kpc (Ortolani et al 2019) and approximate extinction in this direction A V ≈ 2.4 mag (based on the interstellar calculator pro-vided in Nataf et al 2013), we find that the star with the observed brightness F606W ≈ 21.2 mag (broad V band) would have an absolute brightness M V ≈ +4.1 mag, which is a typical value for UCXBs (Nelemans et al 2010).…”
Section: Discussionmentioning
confidence: 69%
“…The X-ray modeling was performed using the Sherpa package (Freeman et al 2001). The total unabsorbed flux in the range 0.5-10 keV is 4.8 +0.5 −0.6 × 10 −13 erg s −1 cm −2 , which corresponds to the luminosity of 4.4±0.5×10 33 erg s −1 , assuming the source is associated with the cluster at the distance of 8.75 kpc (Ortolani et al 2019). In the lower panel of Fig.…”
Section: Investigation Of the Nature Of The New Objectmentioning
confidence: 92%
“…For instance, Kerber et al (2018) applied a similar likelihood function, but comparing synthetic and observed fiducial lines instead of considering all stars. SIRIUS was already applied in Kerber et al (2019) and Ortolani et al (2019).…”
Section: Isochrone Fitting Methodsmentioning
confidence: 99%
“…The parameter t t1 5 determines the starting value of the SFR as sf r t (0 Gyr) = t γ t1 (1 − e −βtt2 ), and t p − t t2 is the maximum age of the thick-disk population with t p being the disk's present-day age. The value of t p is set to 13 Gyr to be consistent with the typical age estimates derived for the oldest globular clusters in the Galactic bulge and halo (de la Fuente Marcos et al 2015;Ortolani et al 2019). With a time resolution of ∆t = 25 Myr, this results in 160 isothermal subpopulations for the thick disk.…”
Section: Thin and Thick Diskmentioning
confidence: 99%